Tracing Compositional and Writing Processes in Sources to the Choral Works of Niels W. Gade - Moe, Bjarke (Danish Yearbook of Musicology, 2019)
The article investigates how Niels W. Gade composed his choral works and how he used written media during the process of composing. A point of departure for the interpretation of the surviving sources is that the preparation of musical manuscripts happened within a socio-musical context, governed by norms dependent on the writer and on the receiver of the text. The article demonstrates that Gade did not follow a single writing procedure when composing his choral works. Gade started out sketching new works at various stages during the creative process of composing. His methods of writing down the musical contents varied too, from scattered notation making only sense to himself to elaborate scores with a high level of details. Even if he might have had a fixed structure of a work in his mind, he often reworked a composition several times before reaching a satisfying version. During the process of writing down his ideas, he made changes to the structure of the music and, while adding details related to the performance of a work, he would revise the composition further. Gade used the written media as a tool during composing, and thus the article argues that writing down a composition was not the goal in itself. The process of notating musical ideas served the purpose of seizing certain element of a work in order to develop the composition further or to distribute information to others. The contents relied on the purpose of the written medium, and so Gade seems to have been conscious of what to write and how to write it. The multifunctional fair copies that he prepared for others to use show that Gade adapted to the situation and changed his ways of working out a composition in order to comply with the demands of others.